India's integration into the world economy: Intensifying, but still ample potential for improvement - Claus-Friedrich Laaser; Astrid Rosenschon (Institut für Weltwirtschaft (IfW), 2018)
With respect to its GDP of markedly more than USD 2,000 bn, India is the seventh largest economy in the world, with respect to population it is even the second largest. Therefore, India has a substantial market potential. The authors analyze in how far the fast growing Indian economy has unexploited options to integrate itself into the international division of labor, to what extent India is actually integrated into the world economy, and what are the country's regional and sectoral trade patterns. So far, India is trading intensely with some specific partners, the USA and particularly the Arabian countries, and with crude oil, oil products, and intermediate and finalized products of the jewelry industry. However, European partners are only of minor importance. – – Auf Basis des BIP ist Indien die siebtbedeutendste Volkswirtschaft der Welt und von der Bevölkerungszahl her sogar die zweitbedeutendste, so dass Indien potentiell ein attraktiver Markt ist. Die Autoren analysieren, inwieweit Indien als wichtige und in den letzten Jahren rasch wachsende Volkswirtschaft Spielraum bei der Integration in die Weltmärkte ungenutzt gelassen hat, inwieweit Indien tatsächlich in die Weltmärkte integriert ist und mit wem und mit welchen Produkten das Land vorwiegend handelt. Sie kommen zu dem Ergebnis, dass insbesondere die USA und die Golfstaaten herausragende Handelspartner sind und spezifische Produkte, wie Öl- und Ölerzeugnisse sowie Erzeugnisse der Schmuckindustrie, eine wichtige Rolle spielen. Europäische Länder sind hingegen nur von untergeordneter Bedeutung.
Keywords: 330